Desenvolvimento de dispersões sólidas: Incremento da solubilidade da rutina - Macêdo, Isabelly da Silva Venâncio de (2017)
In recent decades to expand the development of nutraceuticals from the use of plants containing active metabolites for the support not treating various diseases.The rutin is a naturally occurring flavonoid widely known to exhibit a variety of pharmacological activities, such as antioxidant, antiplatelet and antitumor agonist making it a promising candidate for nutraceuticals for chemoprevention purposes. However, its low solubility in aqueous media hinders its permeation in biological systems, thus reducing its therapeutic activity. The development of solid dispersions has been shown to be an effective technique for promoting the increase of aqueous solubility of drugs. The aim of this work was to produce solid dispersion microparticles of rutin, aiming to increase their aqueous solubility. The microparticles were produced by spray-drying using a Box-Behnken factorial design. It was used as carrier polyvinylpyrrolidone (PVP K-30) and for drying colloidal silicon dioxide (Aerosil® 200). The variables of the process studied were the temperature, percentage of rutin and the percentage of Aerosil, totaling 15 experiments. Physical mixtures of the active compound with adjuvants in 1: 1 and 1:9 ratios were also prepared. The results obtained were analyzed by the surface response technique (ANOVA). The evaluated parameters, besides the aqueous solubility, were yield, moisture content, solubility, dissolution in vitro. The microparticles as well as the physical mixtures were characterized by thermal analysis techniques: differential thermal analysis and thermogravimetry, X-ray diffraction and scanning electron microscopy. Statistical analysis showed that the yield was influenced by only one variable, while the moisture content was influenced directly by temperature in combination with the percentage of aerosil. The microparticles showed good yield (31% - 52%) and low moisture content (lessthan 2%). Regarding the solubility, there was no significant change between the microparticles related to the studied parameters. However, there was a significant increase in the solubility of the microparticles when related to the pure drug, with a solubility increase of up to 9 times, besides the excellent increase in the dissolution profile of the drug. Regarding thermal analysis and complementary techniques, the results showed good thermal and physical stability profile of the microparticles. Therefore, the development of microparticulate solid dispersions containing rutin by spray drying was able to increase the solubility of this flavonoid, making it a potential candidate as a nutraceutical for use in complementary diets.